Therapeutic Borderlands: Austerity, Maternal HIV Treatment, and the Elusive End of AIDS in Mozambique. (8th October 2020) - Chapman, Rachel R.
Abstract: "End of AIDS" requires ambitious testing, treatment, and adherence benchmarks, like UNAIDS' "90‐90‐90 by 2020." Mozambique's efforts to improve essential maternal/infant antiretroviral treatment (ART) exposes how austerity‐related health system short‐falls impede public HIV/AIDS service‐delivery and hinder effective maternal ART and adherence. In therapeutic borderland s—where household impoverishment intersects with health‐system impoverishment—HIV+ women and over‐worked care‐providers circumnavigate scarcity and stigma. Worrisome patterns of precarious use emerge—perinatal ART under‐utilization, delayed initiation, intermittent adherence, and low retention. Ending HIV/AIDS requires ending austerity and reinvesting in a public sector health workforce to ensure universal health coverage as household and community safety nets.